Teleclassroom methodology as a tool for correcting school flow with emphasis on the principles of solidarity economy - Bezerra, Rosicleide da Silva; Lima, Lenilde Mérgia Ribeiro; Lima, Lígia Maria Ribeiro (Seven Editora, 2024)
One of the major concerns in the area of education has been the low teaching-learning ratio. As a result, some tools have been used in the classroom to increase the efficiency of student learning. The Telessala methodology bets on the technology of video classes to enable the completion of basic education. Thus, the present work aimed to analyze the possible use of this methodology in the teaching of the Solidarity Economy theme in a class of the Alumbrar project, in the final years of Elementary School, in a state school in the municipality of Sumé-PB. This project focuses on promoting the correction of the school flow of students aged between 13 and 17 years. To this end, bibliographic and field research and qualitative methods were used. For data collection, a semi-structured questionnaire was used, which was applied to the students and the teacher of that class. According to the data analysis, it was concluded that the project developed from the perspective of the Telessala methodology brought numerous contributions to the formation of the students, as there was progress both in the personal and social spheres, as well as in the educational one. Thus, it was realized that the methodology used in the project is viable for the teaching of Solidarity Economy, since it provides an alternative for insertion in the world of work, as well as the strengthening of the perception of citizenship by students. DOI:https://doi.org/10.56238/sevened2024.018-036